Physiological Basis of Effect of Glucocorticoids on Metabolic Processes and Immune System Activity - Mannonovna, Rahimova Madina; Baxtiyorovna, Raxmanova Marjona (American Journal of Biomedicine and Pharmacy, 2025)
Glucocorticoids are essential steroid hormones that play a central role in maintaining metabolic stability and regulating immune responses, particularly during stress and inflammatory conditions. Secreted primarily by the adrenal cortex, these hormones influence carbohydrate, protein, and lipid metabolism while exerting powerful modulatory effects on innate and adaptive immunity. This article analyzes the physiological mechanisms through which glucocorticoids alter metabolic pathways and immune cell function, emphasizing receptor-mediated gene regulation and systemic adaptation. Special attention is given to the dual nature of glucocorticoid action, highlighting their protective role in acute stress and inflammation as well as their potential contribution to metabolic and immune dysregulation during prolonged exposure. Understanding these mechanisms is critical for interpreting stress-related disorders and optimizing the clinical use of glucocorticoid therapy. Glucocorticoids are steroid mediators that exert wide-ranging influence over energy regulation and immune defense mechanisms. Their secretion increases in response to physiological challenges, allowing the organism to adapt by redistributing metabolic resources and controlling inflammatory activity. These hormones act through intracellular receptors that modify gene expression, thereby coordinating cellular metabolism and immune cell behavior. This overview focuses on the systemic consequences of glucocorticoid action, emphasizing how balanced secretion supports adaptation, whereas prolonged or excessive exposure leads to metabolic imbalance and weakened immune protection.